Anchoring PhD and Doctor of Nursing Practice programs through integration of real-world data and pragmatic research. - Nahm, Eun-Shim; Yarnell, Amy; Seidl, Kristin; Moscou-Jackson, Gyasi; Chen, Lynn; Park, Jiwon; Idzik, Shannon (Nursing Outlook, 2025)
Recently, there has been strong focus on applying pragmatic research (PR) methods and real-world data (RWD) in healthcare. These approaches allow researchers to test interventions in real-world settings. This field underscores the complementary roles of nursing PhD and DNP programs. The RWD-PR field can serve as a unifying anchor for both programs and may also reignite nurses' interest in the PhD pathway. To present strategies for the development and implementation of the RWD-PR courses, along with findings from evaluations and lessons learned. In a planning grant project, our interdisciplinary team developed and pilot-implemented an RWD-PR certificate program using a phased, co-design approach. Once developed, the courses were piloted virtually with PhD and DNP students. Findings suggested significant potential for drawing on complementary strengths of both PhD and DNP programs in applying PR and RWD analytics. This project contributes to the body of knowledge in doctoral nursing education and provides a scalable, adaptable framework for PhD-DNP partnerships that can advance nursing science and practice. • PhD and DNP programs can synergistically impact healthcare research and practice. • Pragmatic research (PR) and real-world data (RWD) can serve as a unifying anchor for both programs. • Findings from developing and implementing the RWD-PR certificate reaffirmed potential. • Co-design approaches ensured course alignment with PhD and DNP education needs. • Virtual labs and hands-on sessions improved engagement in research and analytics.